Sketching Enactive Interactions - Rodríguez, Andrés Santiago (2020)
The growing trend to integrate the physical form and the digital process affects all the disciplines involved in the design of interactive systems. From a computing perspective, it means creating both embodied and contextual interfaces (which use physical objects to control digital information and depend on the signals available in the environment and situation). Designing has been considered central to HCI with different turns from a focus on the design of software to the current family of user-centered design processes. Theories of Cognition that understand it as an embodied, situated, and enactive phenomenon have expanded notably and opened new research programs in HCI. In recent decades there was a shift towards embodiment with the intention of understanding the interaction with the social and physical environment and the design of supporting interactive systems. The focus of this thesis is constituted in the intersection of three topics of current interest for HCI: a) the designing of interactive systems, with an emphasis on the creation of interaction mechanisms that combine one foot in the digital and one in the physical: how to cope in practice with the challenge of integrating physical form with digital software?; b) the available support of new theories of embodied and enactive cognition: how to approximate the design of interactive systems taking into account explicitly that the cognition that users have of them is embodied and enactive?; c) the creative process supported by sketching, a tool par excellence for the design of interactions: what are the similarities and differences between freehand sketching and enactive interaction sketches? How should the supporting tools be?